2015
DOI: 10.1007/s00213-015-4176-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lisdexamfetamine and s-citalopram, alone and in combination, on effort-related choice behavior in the rat

Abstract: LDX can increase work output in rats responding on effort-based choice tasks, which may have implications for understanding the neurochemistry of motivational symptoms in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 79 publications
6
63
0
Order By: Relevance
“…Moreover, chronic IFN-α administration reduced effort-based but not freely available sucrose consumption by the monkeys (Felger et al, 2013c). Similar to the effects of IFN-α, peripheral administration of IL-1β to rodents has been shown to decrease effortful responding for sucrose reward over freely available chow, in the absence of a decrease in preference for freely available sucrose over chow (Nunes et al, 2014); an effect that was reversed by lisdexamfetamine (Yohn et al, 2016). Interestingly, peripheral administration of IL-1β in mice at 24 h has been shown to decrease locomotor (wheel running) activity, which was improved by methylphenidate but not modafinil (Bonsall et al, 2015).…”
Section: Biochemical and Behavioral Studies In Laboratory Animalsmentioning
confidence: 85%
“…Moreover, chronic IFN-α administration reduced effort-based but not freely available sucrose consumption by the monkeys (Felger et al, 2013c). Similar to the effects of IFN-α, peripheral administration of IL-1β to rodents has been shown to decrease effortful responding for sucrose reward over freely available chow, in the absence of a decrease in preference for freely available sucrose over chow (Nunes et al, 2014); an effect that was reversed by lisdexamfetamine (Yohn et al, 2016). Interestingly, peripheral administration of IL-1β in mice at 24 h has been shown to decrease locomotor (wheel running) activity, which was improved by methylphenidate but not modafinil (Bonsall et al, 2015).…”
Section: Biochemical and Behavioral Studies In Laboratory Animalsmentioning
confidence: 85%
“…Previous studies have shown that administration of TBZ had no significant effect on free food intake in both mice and rats (Nunes et al, 2013;Pardo et al, 2015;Correa et al, 2018;López-Cruz et al, 2018) and did not induce changes in hedonic taste reactivity to sucrose (Pardo et al, 2015). In rats responding on effort-based choice tasks involving lever pressing, TBZ-induced decreases in lever pressing are actually accompanied by increased intake of the concurrently available chow (Nunes et al, 2013;Yohn et al, 2016b). Taken together, these data are consistent with other studies indicating that the TBZ-induced relative shifts in choice behavior do not appear to be due to changes in primary food motivation (Randall et al, 2012(Randall et al, , 2014Nunes et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Diverse tasks have been used in rodents for evaluating behavioral activation and effort-related decision making, including tasks that give animals the option of vigorously working (lever pressing or climbing a barrier) to obtain access to more highly valued reinforcers vs. approaching and consuming a less preferred reinforcer (Cousins et al, 1994;Salamone and Correa, 2002;Salamone et al, 2016;Mott et al, 2009;Mai et al, 2012;Pardo et al, 2012Pardo et al, , 2015Randall et al, 2012;Sommer et al, 2014;Yohn et al, 2015aYohn et al, , 2016bCorrea et al, 2018;SanMiguel et al, 2019). In these tasks, conditions that alter DA transmission, such as administration of DA antagonists or tetrabenazine (TBZ), can alter behavioral activation and reduce selection of high-effort choices in rats (Nunes et al, 2013;Randall et al, 2014;Hosking et al, 2015;Pardo et al, 2015;Yohn et al, 2015aYohn et al, , 2016aContreras-Mora et al, 2018;Rotolo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This pattern of responding generates a relatively low 756 baseline rate of PROG lever pressing that can be sensitive to drugs that increase behavioral activation. Several DA transport blockers can increase selection of high-effort PROG lever pressing when administered on their own, including MRZ-9547 (Sommer et al, 2014), bupropion (Randall et al, 2015b;Salamone et al, 2016a), lisdexamfetamine (Yohn et al, 2016e), PRX-14040 (Yohn et al, 2016d), and GBR12909 . These results are consistent with studies reporting that there is enhanced selection of high-effort instrumental actions in mice with knockdown of DA transporters (Cagniard et al, 2006), and in mice that have increased expression of DA D2 receptors in nucleus accumbens induced during adulthood (Trifilieff et al, 2013).…”
Section: Pharmacology Of Effort-relatedmentioning
confidence: 99%
“…Other studies in animals have involved direct administration of the proinflammatory cytokines interleukin (IL)-1b and IL-6. In rats tested on the FR5/chow-feeding choice task, a low-effort bias was induced by administration of IL-1b (Nunes et al, 2014;Yohn et al, 2016e) and IL-6 at doses that did not alter food preference or induce fever. These effort-related effects of cytokine administration were reversed by the adenosine A 2A antagonist MSX-3, and also by the DA transport inhibitors lisdexamfetamine and methylphenidate (Nunes et al, 2014;Yohn et al, 2016a,e).…”
Section: Pharmacology Of Effort-relatedmentioning
confidence: 99%